An independent foreign policy for Canada? : challenges and choices for the future - Bow, Brian J.; Lennox, Patrick (University of Toronto Press, 2008)
Divided into sections about the history of Canadian foreign policy, diplomacy, security, economics, decision-making and new policy issues, this collection of prominent political scientists provides valuable and timely perspectives on the state of Canada's international relations in the twenty-first century.